2010
DOI: 10.5539/res.v2n2p3
|View full text |Cite
|
Sign up to set email alerts
|

What about Us? Measuring the Work-Life Balance of People Who Do Not Have Children

Abstract: To date, the work-family literature has examined conflict between work and family and family and work. In this research the use of the word "family" usually denotes child-care responsibilities. Furthermore, scales developed to measure conflict have concentrated on a family structure defined in this way. Little is known about conflict between work and non-work experienced by people who do not live within a family structure that includes children. The aim of this paper is to examine whether existing work-family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…7 Recent research has suggested that traditional WLB scales do not adequately measure the conflicts experienced by people without children. 8 One frequently used method is to include a single WLB item. The leading researcher in assessing and understanding the prevalence and severity of physician burnout, Dr Tait Shanafelt, uses a single item: 'My work schedule leaves me enough time for my personal/family life' (response options were strongly agree to strongly disagree).…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent research has suggested that traditional WLB scales do not adequately measure the conflicts experienced by people without children. 8 One frequently used method is to include a single WLB item. The leading researcher in assessing and understanding the prevalence and severity of physician burnout, Dr Tait Shanafelt, uses a single item: 'My work schedule leaves me enough time for my personal/family life' (response options were strongly agree to strongly disagree).…”
Section: Introductionmentioning
confidence: 99%
“…Aggregate scores were computed for social networks, social interaction, social support, subjective social support, social and leisure participation, community participation, problems accessing and using services, work-life conflict, stigma consciousness and perceived stereotyping (Hughes, Blazer, & Hybels, 1990;Pinel, 1999;Somers, 1993;Waumsley et al, 2010). Items on paid work status and unemployment were used to compute employment status.…”
Section: Discussionmentioning
confidence: 99%
“…Data on socio-demographics, typologies of women with no children, stigmatisation, stereotyping and exclusion were collected by way of a self-administered online questionnaire. Indicators of exclusion were measured using the social network, social interaction and subjective social support subscales of the Duke Social Support Index (George, Blazer, Hughes, & Fowler, 1989), the MOS social support index (Chronbach's α = 0.97; one-year stability α = 0.78) (Sherbourne & Stewart, 1991) and an adapted social and leisure participation scale (Melbourne Institute of Applied Economic and Social Research, 2012) in the social domain; participation in community groups, activities and events (Australian Bureau of Statistics, 2010), volunteering (Women's Health Australia, 2010), satisfaction with feeling part of the community (Cummins, Eckersley, Pallant, Van Vugt, & Misajon, 2003) and satisfaction with opportunities to have a say on important issues (Pope & Zhang, 2010) in the civic domain; degree of problems accessing and using services (Dermott et al, 2012) in the service domain; and employment status (Melbourne Institute of Applied Economic and Social Research, 2012), personal income (Australian Bureau of Statistics, 2011) and work-life conflict (Waumsley, Houston, & Marks, 2010) in the economic domain.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…The Cronbach's α value for all the dimensions were above the threshold limit i.e., 0.70. Furthermore, work life balance was measured though 5 items generated with the help of previous literature such as (Waumsley et al, 2010). The Cronbach's α values for this construct was found to be greater than 0.70.…”
Section: Instrumentmentioning
confidence: 99%